Поняття та загальні критерії індивідуалізації покарання при призначенні покарання за кримінальним правом України - Бережнюк, Владислав Михайлович (Національний університет "Львівська політехніка", 2021)
У дисертації проведено комплексне кримінально-правове дослідження поняття та загальних критеріїв індивідуалізації покарання при призначенні покарання за кримінальним правом України. Індивідуалізацію покарання визначено одним із базових елементів конструкції взаємопов’язаних завдань кримінального законодавства, принципів кримінальної відповідальності, цілей покарання, інших мір кримінально-правового характеру й основних інститутів кримінального права. Встановлено, що індивідуалізація покарання – це визначення судом виду й конкретної міри покарання на основі врахування індивідуального ступеня тяжкості вчиненого кримінального правопорушення, персоніфікованих якостей особи винного й ряду пом’якшуючих та обтяжуючих покарання обставин, що спрямоване на забезпечення досягнення цілей загальної превенції (відновлення соціальної справедливості) і приватної превенції (виправлення засудженого). Встановлено, що особа винного як загальний критерій індивідуалізації покарання є сукупністю правових, соціальних, психологічних та фізичних властивостей індивіда, визнаного винним у вчиненні кримінального правопорушення, які характеризують особу до моменту вчинення кримінального правопорушення, під час вчинення та після вчинення кримінального правопорушення і мають суттєве значення для вибору міри кримінально-правового впливу з точки зору досягнення мети покарання. З’ясовано, що ступінь тяжкості вчиненого кримінального правопорушення як загальний критерій індивідуалізації покарання є показником індивідуального рівня суспільної небезпеки конкретного посягання, який враховується судом під час призначення покарання. Зазначено, що обставини, які пом’якшують та обтяжують покарання як загальні критерії індивідуалізації покарання знаходяться за межами складу кримінального правопорушення, але при цьому безпосередньо впливають на пом’якшення або обтяження покарання, що призначається судом. В диссертации проведено комплексное уголовно-правовое исследование понятия и общих критериев индивидуализации наказания при назначении наказания по уголовному праву Украины. Индивидуализацию наказания определено одним из базовых элементов конструкции взаимосвязанных задач уголовного законодательства, принципов уголовной ответственности. целей наказания, других мер уголовно-правового характера и основных институтов уголовного права. Установлено, что индивидуализация наказания – это определение судом вида и конкретной меры наказания на основе учета индивидуальной степени тяжести совершенного уголовного преступления персонифицированных качеств личности виновного и ряда смягчающих и отягчающих наказание обстоятельств, направленное на обеспечение достижения целей общей превенции (восстановление социальной справедливости) и частной превенции (исправление осужденного). Установлено, что лицо виновного как общий критерий индивидуализации наказания является совокупностью правовых, социальных, психологических и физических свойств индивида, признанного виновным в совершении уголовного преступления, характеризирующих лицо к моменту совершения уголовного преступления во время совершения и после совершения уголовного преступления и имеют существенное значение для выбора мер уголовно-правового воздействия с точки зрения достижения цели наказания. Установлено, что степень тяжести совершенного уголовного преступления как общий критерий индивидуализации наказания является показателем индивидуального уровня общественной опасности конкретного посягательства, который учитывается судом при назначении наказания. Отмечено, что обстоятельства, смягчающие и отягчающие наказание как общие критерии индивидуализации наказания находятся за пределами состава уголовного преступления, но при этом непосредственно влияют на смягчение или обременение наказания, назначаемого судом. The dissertation deals with the comprehensive criminal law study of the concept and general criteria of individualization of punishment in sentencing under criminal law of Ukraine. The individualization of punishment is defined as one of the basic elements of the construction of interrelated tasks of criminal legislation, principles of criminal liability, purposes of punishment, and other measures of criminal law and the main institutions of criminal law. It is established that individualization of punishment is the determination of the type and specific measure of punishment by the court. It is based on the individual degree of seriousness of a criminal offense, personalized qualities of the perpetrator and a number of mitigating and aggravating circumstances aimed at ensuring the goals of general prevention (rectification of social justice) and private prevention (correction of the convict). That the formal side of justice is directly related to the individualization of punishment and provides for the fullest and most comprehensive consideration of all criteria for sentencing so that latter is commensurate with the offense. A fair punishment can be imposed only in accordance with the requirement of its individualization, just as the individualization of punishment cannot be achieved if the sentence imposed is unjust. Is justified by the prejudice of the fact that in conditions when the criminal law is a generalization of a typical situation of a criminal offense, contains an abstract formulation , is general, and the actions and the person of the offender - specific, respectively, the solution of the above problem is impossible without a certain «operational» scope of action provided by the court, which in relation to knowledge of a single case is a necessary prerequisite for individualization of punishment. It is noted that determining the punishment measure without individual consideration of specific features of the criminal offense, the perpetrator, a number of mitigating and aggravating circumstances is in clear contradiction with the principles of punishment fixed in criminal law – fairness, individualization, differentiation, and adequacy. It is notes that the person guilty in its structure and relationship with the external environment is a very complex system that combines biogenic, phychogenic and sociogenic substructures. It is concluded that the study of the perpetrator should be based on an expanded interpretation of the characteristics of such a person, which will achieve the goal of punishment and implement the principle of individualization of punishment in its appointment. Analyzed the approaches of «openness» and «exhaustiveness» of the list of mitigating and aggravating circumstances in sentencing. It has been proved that it is inexpedient to absolutes the formalization of the rules of talking into account the circumstances that mitigate aggravating punishments when determining the degree of criminal punishment. It is proved that a perpetrator of a crime as a general criterion of individualization of punishment is a set of legal, social, psychological and physical characteristics of the individual found guilty of a criminal offense, which characterize the person before, during and after the commission of criminal offense. They are essential for choice of the degree of criminal law influence in terms of achieving the purpose of punishment. The degree of seriousness of a criminal offense as a general criterion of individualization of punishment is an indicator of the individual level of social danger of a particular encroachment, which is taken into account by the court in sentencing. The essence of social danger is the objective ability of certain types of actions to lead to negative changes in social reality, to disrupt the system of social relations, to deform and introduce elements of disorganization into a particular system of law and order. It is noted that it is expedient to objectively measure the social danger of a crime from the position in which the instruments of such measurement are the nature and degree of public danger. The approaches of «openness» and «exhaustiveness» of the list of circumstances aggravating punishment in sentencing are analyzed. It is proved that it is inexpedient to absolutes the formalization of the rules of taking into account the circumstances that aggravate the punishment when determining the degree of criminal punishment. It is noted that mitigating and aggravating circumstances as general criteria of individualization of punishment are outside the components of the criminal offense, but they directly affect the mitigation or aggravation of the sentence imposed by the court. Without systematic analysis and detailed consideration and further motivation in the sentence of mitigating and aggravating circumstances, the court’s sentence, which determines the size of the sentence, cannot meet the requirements of individualization, fairness and persuasiveness.
Понятие и общие критерии индивидуализации наказания при назначении наказания по уголовному праву Украины
The concept and general criteria of individualization of punishment in sentencing under criminal law of Ukraine
Keywords: індивідуалізація покарання; призначення покарання; загальні критерії індивідуалізації покарання; особа винного; ступінь тяжкості вчиненого кримінального правопорушення; обставини, що обтяжують покарання; обставини, що пом’якшують покарання; суддівський розсуд; диференціація відповідальності; индивидуализация наказания; назначение наказания; общие критерии индивидуализации наказания; лицо виновного; степень тяжести совершенного уголовного преступления; обстоятельства, отягчающие наказание; обстоятельства, смягчающие наказание; судейское усмотрение; дифференциация ответственности; individualization of punishment; sentencing; general criteria of individualization of punishment; perpetrator; degree of seriousness of a criminal offense; aggravating circumstances; mitigating circumstances; judicial discretion; differentiation of liability; 343.28/29(477)